2015
DOI: 10.1371/journal.pone.0144131
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Role of Relationship Life Events in the Onset of Depression during Pregnancy and the Postpartum

Abstract: BackgroundThe precipitating role of life events in the onset of depression is well-established. The present study sought to examine whether life events hypothesised to be personally salient would be more strongly associated with depression than other life events. In a sample of women making the first transition to parenthood, we hypothesised that negative events related to the partner relationship would be particularly salient and thus more strongly predictive of depression than other events.MethodsA community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 52 publications
5
18
1
Order By: Relevance
“…Interestingly, previous studies suggest some heterogeneity across countries in relation to whom women draw on for support. Studies in high income countries have found that mothers rely on coping resources from within their close interpersonal relationships [13], while a study conducted in Malawi found that women believed that a lack of financial or emotional support from friends and family members during the perinatal period was a risk factor for mental distress [60].…”
Section: Unadjusted or (95% Ci)mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, previous studies suggest some heterogeneity across countries in relation to whom women draw on for support. Studies in high income countries have found that mothers rely on coping resources from within their close interpersonal relationships [13], while a study conducted in Malawi found that women believed that a lack of financial or emotional support from friends and family members during the perinatal period was a risk factor for mental distress [60].…”
Section: Unadjusted or (95% Ci)mentioning
confidence: 99%
“…Stressful life events (SLEs) are events that negatively influence the way a household typically lives [9]. A small body of literature, primarily conducted in high income countries, examines the association between exposure to SLEs and MMD [10][11][12][13][14]. A study in Nepal found that women 5-10 weeks postpartum who experienced a SLE in the year prior to the study had 4.6 times the odds of postnatal depression compared to women who had not experienced a SLE [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been determined that social support is a very important (O'Hara and Swain 1996) and protective factor in postpartum depression (Reid and Taylor 2015). In this respect, considering the importance of couple relationship in postpartum depression (Wright et al 2015), it is argued that especially partner support may be important. Since the relationship established with the partner is one of the most important interpersonal relationships in individual's life (Whisman and Baucom 2012), it is stated that in addition to being a good source of emotional support in the postpartum period, partner may be a source of instrumental support by helping with child care and homerelated tasks (Dennis 2003).…”
Section: Partner Supportmentioning
confidence: 99%
“…Transition to motherhood is an important process of change for women and this process represents an emotionally quite difficult and unsteady period (Gotlib et al 1991). For this reason, it is thought that a safe and supportive partner relationship plays a very important role in coping with the problems in this period in a healthy way (Wright et al 2015). In the light of the literature findings, the aim of this review article is to provide a comprehensive review of some relational variables having an influence on postpartum depression.…”
mentioning
confidence: 99%
“…Poor social support (37), poverty (38), and childbirth without the presence of relatives (39), history of depression (40), and poor woman autonomy (41) from socio-demographic variables, multi-parity (42), prime-parity (43,44), multiple children at home (45), negative attitude toward to one's pregnancy (22,(46)(47)(48)(49), depression during pregnancy (42,50), premarital pregnancy (51,52), miscarriage (53), and prenatal high anxiety(47) from pregnancy and newborn related factors, alcohol use in the husband (54), intimate partner violence (22,55,56), poor husbands education (45), husbands unemployment (46,57), and psychiatric problems in the husband (58) among husband related factors were among the associated factors for the development of postpartum depression. In the context of Ethiopia too, poor marital relation (27,29,32,34,35,59), unplanned pregnancy (21,22,24,27,29,32,34), previous history of depression (21,27,28,34), domestic violence…”
Section: Introductionmentioning
confidence: 99%